(3HjGf aYd GdNjQs - (3Ydj Hf (B((3SdWGf(B) (3eMeO, fhQ GdOjf GdedG GdgQhj GdbGQj,J (B1014 (3g` s ((3Ydi GdebOSi GdMfai s)
(3ChdgG (B:s
(3GdMeO ddg hcai hSdGeg Ydi YHGOg GdPjf EUWai CeG HYO ajbhd Gfg hbYJ eSFdI EVWQH ajgG abgGA GdYUQ hgj Cf GdCaGbi GdMGL Yf GdZjQ EPG JLGhR Yf GdejbGJ s
(3BNQgG (B:s
(3LhGHg GdMeO ddg jQLY hjMQe ef GdejbGJ GdeYjf deKdg hGddg SHMGfg hJYGdi CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B8s
(3GdfSNI HgG MhGTs
(3QSGdI ai GdML Yf GdZjQ GPG JLGhR GdejbGJ HZjQ GMQGe hJSei HjGf aYd GdNjQs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B12 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B100s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs